(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
In this article, we discuss the history of Chinese hieroglyphs, the creation of pictographs and ideograms, the meaning of complex hieroglyphs and foreign words, and how complex hieroglyphs are made, and the phenomenon of joining two hieroglyphs together or similar